Contribution of nonesterified fatty acids to mitogen-activated protein kinase activation in human skeletal muscle during endurance exercise - Zbinden-Foncea, H.; van Loon, L. J. C.; Raymackers, J. M.; Francaux, M.; Deldicque. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
Mitogen-activated protein kinase (MAPK) pathways are activated in skeletal muscle during endurance exercise, but the upstream molecular events are incompletely resolved. As an increase in plasma nonesterified fatty acids (NEFA) is a common feature of long-lasting exercise, the authors tested the hypothesis that NEFA contribute to the activation of MAPK during endurance exercise. Acipimox was used before and during endurance exercise to prevent the elevation of plasma NEFA levels in healthy subjects and patients with diabetes. In 2 separate studies, healthy subjects cycled for 2 hr and patients with diabetes for 1 hr at 50% Wmax. In control conditions, plasma NEFA concentrations increased from 0.35 to 0.90 mM during exercise in healthy subjects and from 0.55 to 0.70 mM in patients with diabetes (p < .05). Phosphorylation states of extracellularly regulated kinase 1 and 2 (ERK1/2), p38, and c-Jun NH2-terminal kinases (JNK) were significantly increased after exercise in the vastus lateralis in both groups. Acipimox blocked the increase in plasma NEFA concentrations and almost completely repressed any rise in ERK1/2 and p38 but not in JNK. In conclusion, the data support a role for plasma NEFA in the activation of p38 and ERK1/2 in skeletal-muscle tissue of healthy and diabetic subjects during endurance exercise. Further investigation will be required to determine the molecular link between NEFA and MAPK activation during exercise in human skeletal muscle.